Przekład w przestrzeni oddziaływania obcej kultury - Simeonova‑Konach, Galia (Przekłady Literatur Słowiańskich, 2015)
Translation in the sphere of foreign culture This article examines the problems associated with the acceptance of the work of Tadeusz Konwicki in Bulgaria and Yordan Yovkov in Poland. The fundamental questions in the field of translation studies are considered in this article, which are related to the different cultural code of the recipient, historical difficulties and incorrect translation strategies. Key words: translation, reception, historical and cultural discourse, Tadeusz Konwicki, Yordan Yovkov, the Exotic Other